Directly monitoring the active sites of charge transfer in heterocycles in situ and in real time. Issue 4 (17th December 2018) - Ye, Shuji; Tan, Junjun; Tian, Kangzhen; Li, Chuanzhao; Zhang, Jiahui; Luo, Yi
Abstract : Coherent degenerate infrared-infrared-visible sum frequency generation vibrational spectroscopy provides a powerful label-free probe for identifying the vibrational modes that are coupled through the electronic states in situ and in real time. Abstract : Coherent degenerate infrared-infrared-visible sum frequency generation vibrational spectroscopy provides a powerful label-free sensitive probe for charge transfer active sites in heterocyclic molecules in situ and in real time.